Zmienność częstości i charakteru przebiegu zjawisk lodowych na rzece Parsęcie w aspekcie zmian klimatycznych - Łukaszewicz, Jan; Jawgiel, Kamil (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The article presents the frequency, occurrence and variability of ice phenomena on the Parsęta River from 1951-2010. The variability of the course and nature of the ice phenomena has been described against the background of the changing climate, with particular emphasis on the variability of the air temperature and the thermodynamics of winter periods. In order to better visualize the variability of the thermals of the individual winter seasons, climatic classification of the individual periods was carried out and the anomalies were determined on the basis of it. The work also includes the course of atmospheric circulation, which determines the course of the air temperature on the river basin. For this purpose, the Jones index has been used, which is calculated to represent the North Atlantic Oscillation (NAO). Based on the research, the shortest and longest periods of ice phenomena have been distinguished and their formation has been determined, depending on the variability of air temperature and water. The division of the ice phenomena into individual types and forms is also included in this article.
Keywords: ice phenomena; the Parsęta River; variability of air temperature; river ice; North Atlantic oscillation (NAO)